An examination of the territorial imbalance of the cruising activity in the main Mediterranean port destinations: Effects on sustainable transport. (April 2018) - Rosa-Jiménez, Carlos; Perea-Medina, Beatriz; Andrade, María J.; Nebot, Nuria
Abstract: The increase in cruise activity in Mediterranean port cities is overwhelming historic centres and tourist resources with implications in traffic congestion. Mobility is an important criterion for cruise destinations, besides being an economic resource for the city. The massification of destinations is forcing the adoption of sustainable approaches based on public transport. Starting with a comparative study of the main Mediterranean cruise ports, we define four indicators to identify different levels of the pressure range relating the volume of passengers to the local population, the level of port infrastructure, and the condition of the homeport. The results are classified into four settings, whose geographical distribution confirms the inherent imbalance of cruise ship activity in the Mediterranean. The dependence of a port on its status as a tourist destination, in addition to its geographical and urban conditions, facilitates the development of sustainable public transport as compared with the main destinations. Highlights: Shows the territorial imbalance of cruise activity in main Mediterranean cruise ports. Classifies the main Mediterranean cruise ports in four categories, according to their urban and transport features. Demonstrates the main European continental homeports are the major cultural tourist destinations. Emphasizes the condition of dependent ports.